PARARELISME DALAM KALIMAT PADA BERITA ONLINE DETIKMEDAN.COM - RIDWAN SYAHPUTRA; JUNIAR . (LP2MTBM MAKARIOZ, 2020)
This research aims at describing pararelism in sentences on online news detikmedan.com reviewed from the alignment ofthe form. The research was conducted on the detikmedan.com online news text. The method used is a qualitative researchmethod directed at the linguistic data. The source of this research data is a sentence in the news text on online newsdetikmedan.com. Sampling is done gradually. The results showed that there were 14 sentences that had proper pararelismin the news text being reviewed from the alignment of the form. There are 10 sentences that have erroneous parerism in thenews text being reviewed from the alignment of the form.